Tosta Evans, 1953 (Lepidoptera: Hesperiidae): a new species from northeast Brazil, first description of the female of Tosta tosta Evans, 1953, and placement of the genus within Achlyodini - Siewert, Ricardo Russo; Mielke, Olaf Hermann Hendrik; Casagrande, Mirna Martins (Zootaxa, 2015)
A new species of Tosta Evans, 1953 from northeast Brazil is described: T. pseudospeculum Siewert, Mielke & Casagrande, sp. nov. Additionally, the female of Tosta tosta Evans, 1953, the type species of the genus, is described for the first time. Illustrations of adults and male and female genitalia for all studied species are provided, as well as a discussion of the placement of the genus within the tribe Achlyodini.